Separation and Identification of Odd Chain Triacylglycerols of the Protozoan Khawkinea quartana and the Mold Mortierella alpina Using LC-MS - Řezanka, Tomáš; Vítová, Milada; Nováková, Alena; Sigler, Karel (Lipids, 2015)
Liquid chromatography-atmospheric pressure chemical ionization mass spectrometry (LC-MS/APCI) with reversed- and chiral phases was used for separation of triacylglycerols (TAG) from protozoan and mold. This study describes the separation and identification of odd numbered chains of regioisomers and enantiomers of triacylglycerols from different natural sources, i.e., the protozoan Khawkinea quartana and the mold Mortierella alpina. Using the above-mentioned separation methods and the synthesis of appropriate standards of TAG, we identified regioisomers and enantiomers of both even and odd numbered TAG. The biosynthesis of odd numbered TAG was found to be strictly stereospecific and to depend on the production microorganism, one enantiomer predominating in the protozoan and the other in the mold. It was proved that even numbered TAG are synthesized in a higher optical purity, which can be explained by a higher affinity of acyltransferases to the respective substrate, i.e., to even chain PUFA.
Keywords: Mass Spectrometry; vysokoúčinná kapalinová chromatografie; Euglena; hmotnostní spektrometrie; Triglycerides; Chromatography, High Pressure Liquid; Mortierella; triglyceridy